1182. The Real-World Use of Isavuconazole as Primary or salvage Therapy of Invasive Fungal infections in High-Risk Patients with Hematologic Malignancy or Stem Cell Transplant. (31st December 2020) - dagher, Hiba; Hachem, Ray Y; Chaftari, Anne-Marie; Jiang, Ying; Ali, Shahnoor; Deeba, Rita; Shah, Shivan; Raad, Issam I; Raad, Issam I
Abstract: Background: Invasive fungal infections (IFIs) are a major cause of morbidity and mortality among immunocompromised patients with hematologic malignancies (HM) and stem cell transplants (SCT). Isavuconazole was approved by FDA as a primary therapy for Invasive Aspergillosis (IA) and Mucormycosis. The aim of this study is to look at the real-world use of Isavuconazole in patients with HM and evaluate their clinical outcomes and safety. Methods: We conducted a retrospective study of 200 HM patients at MD Anderson Cancer Center who had definite, probable or possible mold infections between April 2016 and January 2020 and were treated with Isavuconazole for a period of at least 7 days. Clinical and radiological findings were assessed at baseline and at 6 and 12 weeks of follow up. Results: HM patients with IFIs were classified as definite (11), probable (66) and possible (123). IA was the most commonly isolated pathogen followed by mucor and candida. The majority of patients (65%) received prophylaxis with anti-mold therapy, 73% consisted of azoles and 22% of echinocandins. Isavuconazole was used as a primary therapy in 57.5% of patients, and as salvage therapy in 42.5%. The switch to Isavuconazole was driven by failure of the primary therapy in 50% of the cases and by adverse effects in 28%. These included elevated liver function tests (LFTs), subtherapeutic voriconazole levels and prolonged QT. Isavuconazole was used as monotherapy in 30% of the cases and combination in 70% mostly with a polyene (54%) and/or an echinocandin (27%). A favorable response with Isavuconazole was observed in 57% at 6 weeks of therapy. Adverse events possibly related to Isavuconazole were reported in 6 patients (3%) leading to drug discontinuation. These included 5 elevated transaminases and 1 nausea. All-cause mortality was reported in 46% of patients and IFI-attributable mortality in 25%. Conclusion: Selecting Isavuconazole therapy was mainly driven by failure of other antifungal agents or adverse events to other antifungals such as increased LFTs, subtherapeutic voriconazole levels or prolonged QT. Isavuconazole seems to have a promising clinical response and a good safety profile as an antifungal therapy in high risk cancer patients with HM. Disclosures: Issam I. Raad, MD, Citius (Other Financial or Material Support, Ownership interest)Cook Medical (Grant/Research Support)Inventive Protocol (Other Financial or Material Support, Ownership interest)Novel Anti-Infective Technologies (Shareholder, Other Financial or Material Support, Ownership interest)